A relation of the rare occurrences in a third voyage made by Sir Francis Drake into the West Indies in the years 72 and 73 : when Nombre de Dios was by him and 52 others only in his company surprised - Nicholls, Philip (Adam Matthew Digital, 1570)
Ms. record of Sir Francis Drake's third voyage to the West Indies by Philip Nicholls, based on the reports of Christopher Ceelie, Ellis Hixon and others. Formerly owned by Charles I